2021
DOI: 10.1016/j.jseint.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Increased medial laxity of the elbow in preadolescent baseball players with or without medial elbow apophysitis

Abstract: Background Medial elbow apophysitis is a traction apophysitis observed in the medial epicondyle of the elbow in preadolescent baseball players. The purpose of this study was to determine the relationship between medial elbow apophysitis and elbow valgus instability in preadolescent baseball players. Methods The participants were classified into a control group and an injury group; the injury group included participants diagnosed with a medial elbow injury (inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Adolescent and college-aged baseball players with elbow pain have more medial elbow joint space than players without pain symptoms. 25 , 29 Recently, studies have reported that increasing FDS function increases the medial-side stability in valgus stress and helps to improve baseball players with ulnar collateral ligament injury. 9 , 18 , 22 , 24 Regarding finger movements during pitching motion, the force of the thumb and ring fingers is greatest just before the maximum shoulder external rotation, whereas the force produced from the index and middle fingers reaches the peak just before the maximum shoulder external rotation and ball release.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent and college-aged baseball players with elbow pain have more medial elbow joint space than players without pain symptoms. 25 , 29 Recently, studies have reported that increasing FDS function increases the medial-side stability in valgus stress and helps to improve baseball players with ulnar collateral ligament injury. 9 , 18 , 22 , 24 Regarding finger movements during pitching motion, the force of the thumb and ring fingers is greatest just before the maximum shoulder external rotation, whereas the force produced from the index and middle fingers reaches the peak just before the maximum shoulder external rotation and ball release.…”
Section: Discussionmentioning
confidence: 99%
“…This limb position method for SUS was applied in similar studies. 10 , 11 , 22 , 24 However, it is unclear which limb position method more clearly detects valgus laxity in baseball players.…”
mentioning
confidence: 99%